1995
DOI: 10.1002/cne.903590410
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and glia participate in the removal of apoptotic neurons from the Drosophila embryonic nervous system

Abstract: Cell death in the Drosophila embryonic central nervous system (CNS) proceeds by apoptosis, which is revealed ultrastructurally by nuclear condensation, shrinkage of cytoplasmic volume, and preservation of intracellular organelles. Apoptotic cells do not accumulate in the CNS but are continuously removed and engulfed by phagocytic haemocytes. To determine whether embryonic glia can function as phagocytes, we studied serial electronic microscopic sections of the Drosophila CNS. Apoptotic cells in the nervous sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 59 publications
2
87
1
Order By: Relevance
“…79 In the Drosophila embryo there is some evidence of phagocy- tosis by glial cells. 80 However, the most efficient embryonic phagocytes are professional`macrophages', the phagocytic hemocytes or blood cells.…”
Section: Phagocytosis Is a Crucial ®Nal Step In Apoptosismentioning
confidence: 99%
“…79 In the Drosophila embryo there is some evidence of phagocy- tosis by glial cells. 80 However, the most efficient embryonic phagocytes are professional`macrophages', the phagocytic hemocytes or blood cells.…”
Section: Phagocytosis Is a Crucial ®Nal Step In Apoptosismentioning
confidence: 99%
“…Several studies over the last decade have identified different kinds of apoptotic cells in the CNS (White et al, 1994;Sonnenfeld and Jacobs, 1995;Hidalgo et al, 2001;Peterson et al, 2002;Lundell et al, 2003;Miguel-Aliaga and Thor, 2004;Karcavich and Doe, 2005). In most cases, the developmental signals responsible for inducing PCD in these cells are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have reported PCD occurring in postmitotic differentiated neural cells. Sonnenfeld and Jacobs (Sonnenfeld and Jacobs, 1995) were the first to report degeneration of differentiated midline glial cells upon completing their function in the morphogenesis of commissural axon tracts in early embryogenesis. Hidalgo and colleagues (Hidalgo et al, 2001) showed that survival of longitudinal glia (LG) depends on the Neuregulin trophic factor homolog Vein.…”
Section: Introductionmentioning
confidence: 99%
“…Although the existence of the Drosophila homologue of the gene coding for the macrophage PS receptor has been noted (21), its involvement in phagocytosis in Drosophila is unknown. A large number of cells undergo apoptosis during development of Drosophila and are eliminated through phagocytosis by macrophage-like hemocytes or glia (30,31). In the present study, we examined the mode of phagocytosis of apoptotic cells in Drosophila both in vitro and in vivo, focusing on the involvement of PS on target cells and Croquemort and Draper on phagocytes.…”
mentioning
confidence: 99%